A simple water-soluble phenazine dye for colorimetric/ fluorogenic dual-mode detection and removal of Cu2+ in natural water and plant samples. (December 2019) - Wei, Tai-Bao; Yong, Bi-Rong; Dang, Li-Rong; Zhang, You-Ming; Yao, Hong; Lin, Qi
Abstract: Detection and removal of heavy metal ions in a variety of complex water systems using dyes remains a challenge. Here we have developed a rapid, low-cost, on-site water-soluble dye for the colorimetric/fluorogenic detection and removal of copper ions in natural water and plant samples. By comparing with dye molecule AHP, this water-soluble phenazine dye (AHPN ) has a high fluorescence quantum yield and excellent coordinated ability with copper ions.AHPN can effectively remove copper ions in various natural water samples due to its strong binding ability with Cu 2+ . Moreover, the test strips also were fabricated and successfully used for real-time detection of Cu 2+ in water with simple-to-use, low-cost, quick response and provide an obvious effect by naked-eye. All data in this experiment showed that this water-soluble phenazine dyeAHPN has excellent effect on the detection and removal of Cu 2+ . Graphical abstract: A rapid, low-cost, real-time and water-soluble phenazine dye (AHPN ) was constructed for the colorimetric and fluorogenic detection of copper ions. At the same time, it shows excellent removal ability of copper ions in natural water samples.Image 1 Highlights: A water-soluble phenazine dye (AHPN) was synthesized. AHPN can detect Cu2+ with colorimetric/fluorogenic in water and plant samples. AHPN can effectively remove Cu2+ in natural water samples. The test strips based on phenazine dye AHPN also were fabricated.